Event Study: The Impact of Trump Tax Tariff Announcement On Top Three Sectoral Indices - Muhammad Raffey Satrio Bimo; Jagat Prirayani (Green Publisher Indonesia, 2026)
This study examines the immediate market reaction to the U.S. government’s tariff announcement on April 2, 2025, and evaluates its impact on three key Indonesian sectoral indices: IDXENERGY, IDXBASIC, and IDXFINANCE. Since the announcement was publicly visible and signaled changes in global trade expectations, commodity price movements, and projected profitability in exposed sectors, the study investigates whether the new information was rapidly incorporated into equity prices, in line with the semi-strong form of the Efficient Market Hypothesis (EMH). The research is relevant due to Indonesia’s deep integration into global commodity value chains and financial markets, along with the limited sector-level tariff shock evidence in emerging markets. A short-horizon event study methodology is applied to compute abnormal returns (AR) surrounding the announcement. The Jakarta Composite Index (JCI) serves as the benchmark for estimating expected returns within a 100-day estimation window [–120, –20], and an event window of 21 days [–10, +10] captures anticipatory trading, immediate reactions, and short-term corrections. Abnormal Returns (AR), Average Abnormal Returns (AAR), and Cumulative Abnormal Returns (CAR) are calculated to measure magnitude and persistence. Normality is tested using the Shapiro-Wilk test, and statistical significance is assessed using both one-sample t-tests and Wilcoxon Signed-Rank tests. A market-adjusted model validates robustness. Findings show significant abnormal returns across the entire event window, particularly before the announcement, indicating speculation or rumor-driven trading. Negative abnormal returns peak at T-10, and CAR patterns suggest sustained impact rather than temporary fluctuation.